2022
DOI: 10.1155/2022/6098592
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Protects against Acetaminophen‐Induced Acute Liver Injury by Inhibiting Multiple Endoplasmic Reticulum Stress Pathways

Abstract: Background. Excessive acetaminophen (APAP) use can lead to acute liver injury (ALI) by inducing endoplasmic reticulum stress (ERS). We previously found that pretreatment with the peroxisome proliferator-activated receptor-γ (PPAR-γ) ligand rosiglitazone (RSG) alleviated ALI in APAP-treated mice. Objective. To examine if RSG-mediated hepatoprotection is associated with ERS suppression. Methods. Forty-eight male CD-1 mice were randomly divided into control, RSG, APAP 4 h, APAP 24 h, RSG + APAP 4 h, and RSG + APA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Moreover, evidence has suggested that activation of ERS and apoptosis could cause liver injury, 42 which is consistent with our previous findings in LO2 cells after CTD intervention 8 . Furthermore, suppressing three branches of the ERS signalling pathway could alleviate DILI 43 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, evidence has suggested that activation of ERS and apoptosis could cause liver injury, 42 which is consistent with our previous findings in LO2 cells after CTD intervention 8 . Furthermore, suppressing three branches of the ERS signalling pathway could alleviate DILI 43 …”
Section: Discussionsupporting
confidence: 89%
“…8 Furthermore, suppressing three branches of the ERS signalling pathway could alleviate DILI. 43 To further explore the upstream pathway of apoptosis, the related proteins with ERS including GRP78, PERK, IRE1α, ATF6, ATF4 and CHOP were detected by Western blotting. Our results showed that the administration of CTD could significantly enhance the protein expressions of GRP78, PERK, IRE1α, ATF6, ATF4 and CHOP in mice, indicating that CTD induced ERS response.…”
Section: Integrated Network Analysis To Elucidate the Protective Mech...mentioning
confidence: 99%
“…Treatment with Z-GA resulted in the accumulation of the phosphorylated eIF2α protein, thus relieving the ER stress by attenuation of new protein synthesis. Increased expression of p-eIF2α has been noted in other studies investigating APAP-induced ER stress, which could stem from differences in exposure time and the animal model used. However, the inhibition of eIF2α dephosphorylation caused by Z -GA is hepatoprotective, suggesting an important role for the PERK pathway in APAP toxicity.…”
Section: Resultsmentioning
confidence: 99%